Respuesta :

Answer:

Part A) [tex]sin(2\theta)=\frac{24}{25}[/tex]

Part B) [tex]cos(2\theta)=0[/tex]

Part C) [tex]tan(2\theta)=-\frac{240}{161}[/tex]

Step-by-step explanation:

Part A) we have [tex]cos(\theta)=-\frac{4}{5}[/tex]

θ is in quadrant 3 ----> the sine is negative

Find [tex]sin(2\theta)[/tex]

we know that

[tex]sin(2\theta)=2sin(\theta)cos(\theta)[/tex]

Remember that

[tex]cos^{2} (\theta)+sin^{2} (\theta)=1[/tex]

substitute

[tex](-\frac{4}{5})^{2}+sin^{2} (\theta)=1[/tex]

[tex](\frac{16}{25})+sin^{2} (\theta)=1[/tex]

[tex]sin^{2} (\theta)=1-\frac{16}{25}[/tex]

[tex]sin^{2} (\theta)=\frac{9}{25}[/tex]

[tex]sin(\theta)=-\frac{3}{5}[/tex] ---> remember that the sine is negative (3 quadrant)

Find [tex]sin(2\theta)[/tex]

we have

[tex]cos(\theta)=-\frac{4}{5}[/tex]

[tex]sin(\theta)=-\frac{3}{5}[/tex]

[tex]sin(2\theta)=2sin(\theta)cos(\theta)[/tex]

substitute

[tex]sin(2\theta)=2(-\frac{3}{5})(-\frac{4}{5})[/tex]

[tex]sin(2\theta)=\frac{24}{25}[/tex]

Part B) we have [tex]cos(\theta)=\frac{\sqrt{2}}{2}[/tex]

θ is in quadrant 1

Find [tex]cos(2\theta)[/tex]      

we know that

[tex]cos(2\theta)=2cos^{2} (\theta)-1[/tex]

substitute

[tex]cos(2\theta)=2(\frac{\sqrt{2}}{2} )^{2}-1[/tex]

[tex]cos(2\theta)=0[/tex]

Part C) we have [tex]sin(\theta)=\frac{8}{17}[/tex]

θ is in quadrant 2 ----> the cosine is negative

Find [tex]tan(2\theta)[/tex]  

we know that

[tex]tan(2\theta)=\frac{2tan(\theta)}{1-tan^{2} (\theta)}[/tex]

Remember that

[tex]cos^{2} (\theta)+sin^{2} (\theta)=1[/tex]

substitute

[tex]cos^{2} (\theta)+(\frac{8}{17})^{2}=1[/tex]

[tex]cos^{2} (\theta)=1-\frac{64}{289}[/tex]

[tex]cos^{2} (\theta)=\frac{225}{289}[/tex]

[tex]cos(\theta)=-\frac{15}{17}[/tex]

Find [tex]tan(\theta)[/tex]  

[tex]tan(\theta)=\frac{sin(\theta)}{cos(\theta)}[/tex]

substitute

[tex]tan(\theta)=\frac{(8/17)}{(-15/17)}[/tex]

[tex]tan(\theta)=-\frac{8}{15}[/tex]

Find [tex]tan(2\theta)[/tex]  

[tex]tan(2\theta)=\frac{2tan(\theta)}{1-tan^{2} (\theta)}[/tex]

substitute

[tex]tan(2\theta)=\frac{2(-\frac{8}{15})}{1-(-\frac{8}{15})^{2}}[/tex]

[tex]tan(2\theta)=\frac{(-\frac{16}{15})}{1-(\frac{64}{225})}[/tex]

[tex]tan(2\theta)=\frac{(-\frac{16}{15})}{1-\frac{64}{225}}[/tex]

[tex]tan(2\theta)=\frac{(-\frac{16}{15})}{\frac{161}{225}}[/tex]

[tex]tan(2\theta)=-\frac{240}{161}[/tex]

ACCESS MORE